Committee Members’ Perspectives on Admissions to Canadian Master’s-Level Counselling Programs: Personal Qualities and Gatekeeping Considerations - Gower, Heather K.; Harris, Gregory E. (Canadian Journal of Counselling and Psychotherapy, 2020)
Counsellor personal qualities play a role in admission decisions and counsellor efficacy. However, personal qualities have been sparsely investigated regarding admissions to counselling programs in Canada and internationally. Also, counsellor personal qualities lack clarity for adequate assessment at any regulatory stage. Our preliminary study explored counsellor personal qualities according to Canadian counsellor educators. It explored how these educators represent and reflect upon admissions at their institutions. Six Canadian counsellor educators participated in semi-structured individual interviews. Results demonstrated that personal qualities deemed important by participants for both admissions and practice were largely consistent with the current literature. Most participants preferred that personal qualities be assessed during admissions, typically through interviews. Overall, admissions processes appeared to be inherently subjective regardless of efforts at objectivity. Implications of the study are discussed.